1 - Editorial Note - Journal System (Africa Development, 1984)
This is the result of a very serious research work basically lining the evolution up to 1980 of cereals production, consum exports and imports as well as projections of the same variables up in the various countries studied, putting the accent on the possib exchange among the countries of the sub-region and also the princ tacles and prospects. It is also full of detailed statistical informatio cannot but help anybody who is interested in doing a serious study in changes in consumption patterns in cereals over the last decade o the West African sub-region or the prospects for cereals self-suffic the sub-region level. We cannot possibly exaggerate the importance of the subjec the crisis being faced by agriculture and food production in part the continent and at thè sub-regional level. Such crisis which is recognized by all has been the subject of various «action-programmes» suc Lagos Plan of Action and the World Bank etc.. We, therefore, justif blication not so much because of its theoretical explanation of problem (of which the article is admittedly weak) or for that ma its policy prescriptions (of which it is also weak) but rather on t of data that it provides and which should form the first step tow serious analysis of cereals production and exchange as well as future policies for the West African sub-region.